2013
DOI: 10.1029/2012gc004204
|View full text |Cite
|
Sign up to set email alerts
|

Apparent overconsolidation of mudstones in the Kumano Basin of southwest Japan: Implications for fluid pressure and fluid flow within a forearc setting

Abstract: [1] The Kumano Basin is located in the Nankai Trough subduction zone of southwest Japan. During the past 1.6 million years, approximately 800 meters of sandy turbidites and hemipelagic mud were deposited near the distal edge of the forearc basin, at Site C0002 of the Integrated Ocean Drilling Program. Constant-rate-of-strain consolidation tests yield estimates of in situ permeability that range from 2.6 Â 10 À17 m 2 to 2.5 Â 10 À18 m 2 ; overconsolidation ratios range from 1.7 to 2.6, and values of the compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 103 publications
(148 reference statements)
1
9
1
Order By: Relevance
“…For this range of C v , we predict maximum pore pressures of 0.05–1.6 MPa at the base of the basin section, corresponding to pore pressure ratios of λ * = 0.004–0.13, in good agreement with the observations (where λ * = ( P f − P h )/( P l − P h ), and P f , P h , and P l are the pore fluid pressure, hydrostatic pressure, and lithostatic pressure, respectively) (Figure ). Because this simplified model assumes only one‐dimensional consolidation and fluid flow, any lateral drainage along dipping strata would further enhance drainage [e.g., Guo et al ., ]. If the higher values of permeability obtained from the SP tests are representative of the formation, the corresponding values of C v would be ~2.5 × 10 −7 to ~6 × 10 −6 m 2 /s and would yield even lower pressures (cf.…”
Section: Discussioncontrasting
confidence: 59%
“…For this range of C v , we predict maximum pore pressures of 0.05–1.6 MPa at the base of the basin section, corresponding to pore pressure ratios of λ * = 0.004–0.13, in good agreement with the observations (where λ * = ( P f − P h )/( P l − P h ), and P f , P h , and P l are the pore fluid pressure, hydrostatic pressure, and lithostatic pressure, respectively) (Figure ). Because this simplified model assumes only one‐dimensional consolidation and fluid flow, any lateral drainage along dipping strata would further enhance drainage [e.g., Guo et al ., ]. If the higher values of permeability obtained from the SP tests are representative of the formation, the corresponding values of C v would be ~2.5 × 10 −7 to ~6 × 10 −6 m 2 /s and would yield even lower pressures (cf.…”
Section: Discussioncontrasting
confidence: 59%
“…In all cases the effective stress ratio ( σ ′ 3 / σ ′ 1 ) is 0.27, satisfying the failure criterion for normal faulting given the internal and residual friction angles inferred from conjugate faults. Previous studies have shown that pore fluid pressures are near hydrostatic through much of the Kumano Basin [ Guo et al ., ; Saffer et al ., , ]. This allows us to quantify the magnitude of effective stresses, based on our inversion results and the total overburden stress ( σ v ) defined by integration of density logs.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that even low friction coefficients can allow enough heat generation to cause moderate thermal pressurization. Faults become weaker at high slip rates of > 1 cms −1 , irrespective of rock types and dynamic weakening mechanisms associated with frictional heat (Reches and Lockner, 2010;Di Toro et al, 2011;Han et al, 2011). Among mechanisms of fault weakening, thermal pressurization may be the most efficient at lower heat production and thus may have occurred during at least the beginning of large slip along the shallow plate boundary during the Tohoku earthquake.…”
Section: How Realistic Are Rock Physical Parameters?mentioning
confidence: 96%
“…4 shows the depth distribution of transport properties extrapolated from the results of our laboratory tests, along with Neuzil (1994). Thick dashed lines show the average data of Nankai mudstones (Gamage et al, 2011;Guo et al, 2013) and the conventional cubic law curve. Fig.…”
Section: Transport Propertiesmentioning
confidence: 98%